Las políticas de medioambiente en la UE y el litoral mediterráneo español - Borrell Merlín, María Dolores (Observatorio Medioambiental, 2007)
The environmental policies of the EU are tools to achieve sustainable growth and quality of life. Nevertheless, minimum standards of sustainability are not being applied to the Spanish Mediterranean coastline, where unlimited building is increasing the density and extent of urbanized areas. This destroys the enviroment and endangers the land, a non-renewable resource, and imperils the survival of the large concetrations of populationa expected to live there.
Keywords: Environmental policies; Construction; Land; Spanish Mediterranean coastline